Production and characterization of monoclonal antibodies against leptospira interrogans serovar sanilae - Sathitsemakul, Jaiya; Puthong, Songchan; Patarakul, Kanitha; Palaga, Tanapat; Komolpis, Kittinan (Food and Applied Bioscience Journal, 2017)
Leptospirosis is a widespread zoonotic disease in tropical areas caused by pathogenic gram – negative spirochetes Leptospira spp., which affect both human and animals. The disease is transmitted by contacting urine of the infected animals. Leptospira penetrates through mucosa or open wound skin of infected individuals. Symptoms of leptospirosis are extremely broad such as flu – like illness, red eyes, diarrhea or vomiting. If patients are not diagnosed or treated in time, symptoms can become severe sepsis with multi – organ failure. This study aimed to generate monoclonal antibodies (MAbs) against pathogenic Leptospira spp. that can be used in a development of immunological based assay for early diagnosis of leptospirosis. Mice were immunized with whole cells of fixed Leptospira interrogans serovar Manilae. After conventional cell hybridization technique, all MAbs were screened by enzyme – linked immunosorbent assay (ELISA) with sonicated cell lysates of various serovars of leptospira and other bacteria. The results showed that two MAbs obtained in this study bound specifically with L. interrogans serovar Manilae and serovar Pomona but did not interact with other tested bacteria. The sensitivity indicated by the half maximal effective concentration (EC50) and limit of detection (LOD) by individual MAb was in the range of 4×106–7×106 cells/ml and 4×105–5×105 cells/ml, respectively. Both clones of MAbs were isotyped as IgM. Therefore, these preliminary studies indicated that the obtained MAbs can be used for application in an immunological detection of L. interrogans serovar Manilae.